Factors Influencing the Unification of Safety Culture Within Construction Projects - Lind, Christoffer; Wiksfors, Elin (My University, 2022)
The construction industry has the highest share of fatal workplace accidents and incidents in Sweden, despite the high implementation of laws and regulations regarding safety. Main contractors have the responsibility to make sure that they are providing a safe work environment for the people employed at their construction sites. An important tool to achieve this in the fragmented construction industry, is by having a strong and unified safety culture throughout the project, which consists of attitudes, values, and behaviours towards safety. However, despite the efforts from main contractors to create a strong safety culture that are unified throughout the whole organisation, there are always people that are either not willing, or able, to adapt. This study examines this problem further by investigating how main contractors can facilitate a unified safety culture in construction projects. A case interview study with observations and interviewees from five different construction sites of a major Swedish main contractor was conducted. The interviewees were employed in different organisational levels in building construction projects in Gothenburg and the organisational levels consisted of subcontractors, foremen, site managers and senior executives. The study presents seven predominant factors that enables the main contractor to influence the subcontractors to adapt to their safety culture. These are: Encourage positive communication, Knowledge Sharing, Increased Engagement from Site Management, Language Barriers, Job Satisfaction, Procurement, and long-term relationships with subcontractors. The factors can be investigated further for organisations that wants to increase the unification of the safety culture in construction projects, and the study also mentions several possible enablers to unlock the potential of the discovered factors.
Keywords: Safety Culture in Construction, Accident Prevention, Safety Performance, Project Management, Shared Mental Models, Unified Safety Culture